PSICOLOGÍA, INTERNET Y LA INVESTIGACIÓN CIENTÍFICA - Torres, William (2019)
It is pose the internet issue and the scientific research considering the Psychological implications. It is developed the field related to the use of computers on Psychology emphasizing the work done on Peru and it is mentioned others works around the world too. Then, it is analized the use of internet as a research tool on Psychology pointing out its special characteristics for heuristics endeavours. Also, it is reviewed the psychological research on the internet effect considering, among others issues, the new ways of subjectivity and inter subjectivity.